Sleep, sedentary behavior, and physical activity: A compositional data analysis of 24-hour movement behaviors and executive function in preschool children - Ling Wang; Wanhong Luo; Yong Liu (PLoS ONE, 2026)
Objective This study aims to examine the relationship between 24-h movement behaviors and executive function in preschool children. Methods This cross-sectional study included 266 preschool children (mean age: 3–6 years). Physical activity and sedentary behavior were measured using an accelerometer (ActiGraph GT3X-BT), sleep duration was assessed using sleep logs, and executive function was evaluated using the Early Years Toolbox. Compositional data analysis was then applied to examine the associations among these variables. Results (1) The relative distribution of 24-h movement behaviors was significantly associated with inhibitory control, cognitive flexibility, and working memory (all p < 0.001), with a model explanatory power > 10%. The explanatory power was the highest for inhibitory control (16.3%). (2) After adjusting for other movement behaviors, sedentary behavior was negatively associated with inhibitory control [γ 1 2 = –0.11 (−0.17, −0.05), p < 0.001], cognitive flexibility [γ 1 2 = –1.45 (−2.29, −0.61), p = 0.001], and working memory [γ 1 2 = –0.58 (−0.97, −0.19), p = 0.004]. In contrast, sleep was positively associated with cognitive flexibility [γ 1 1 = 1.60 (0.26, 2.94), p = 0.020]. (3) When 15 min/day of sedentary behavior was isotemporally substituted with sleep, inhibitory control scores increased by 0.003 (0.0004, 0.006), and cognitive flexibility scores increased by 0.064 (0.021,0.106); conversely, replacing sleep with sedentary behavior resulted in a significant decline. Conclusion Reallocating time from sedentary behavior to sleep was positively correlated with executive function, particularly cognitive flexibility. However, most other isotemporal substitution pathways did not show statistically significant effects, providing an important basis for future research to focus on specific behavioral reorganization strategies.